Optimizing Growth And Development Of Toddlers Through Growth And Development Stimulation In RT 25 Sawah Lebar Urban Village, Bengkulu City - Oktavia, Friska; Angelia, Chery; Renita, Renita; Haryanti, Zulmi; Apriyanti, Delta (Universitas Dehasen Bengkulu, 2024)
Kuliah Kerja Nyata atau KKN seeks to solve the problems faced by certain communities, Some of the effects of children's growth and development that are not in accordance with their age include inhibiting brain development, frequent pain / decreased immune system, excessive anxiety or fear, uncontrolled emotions, and cognitive disorders. Other long-term impacts are low reasoning ability and educational achievement as well as low work productivity. The purpose of this service is to increase mother's knowledge about growth and development stimulation for stunting prevention. The method of this activity is distributing leaflets, conducting counseling, and evaluating activities. This activity was held in rt 25 kelurahan sawah lebar kota bengkulu, with the number of participants being 10 mothers with toddlers. The results of the implementation of the activities that we carried out, there was an increase in mother's knowledge after counseling about stimulation of growth and development., this could be seen from the mother's response in the question and answer session. It is hoped that with this service activity, mothers can understand the importance of stimulating growth and development for toddlers and can apply it to everyday life